Characteristics of gym-goers performance-enhancing substance use - Tavares, Ana Sofia (2022)
The use of prohibited performance-enhancing substances (PES) in fitness and gym settings is a public health concern as knowledge concerning its short-term and long-term adverse health consequences are emerging. Understanding the underlying psychosocial mechanisms of PES use and the characteristics of the gym-goers who use PES could help identify those who are most vulnerable to PES use. The aim of this study was to investigate the profile (e.g., sociodemographic factors, exercise profile, gym modalities, peers, and social influence) and psychosocial determinants (e.g., attitudes, subjective norms, beliefs, and intentions) of PES users in gym and fitness contexts. In total, 453 gym-goers (mean age = 35.64 years; SD = 13.08) completed an online survey. Neural networks showed a global profile of PES users characterized by a desire to increase muscle mass, shape their body, and improve physical condition; being advised by friends, training colleagues, and coaches or on the Internet; less formal education, and more positive beliefs for PES use. These results may support public health and clinical interventions to prevent abusive use of PES and improve the health and well-being of gym-goers.